Pengaruh Kepemilikan Institusional, Proporsi Komisaris Independen dan Profitabilitas Terhadap Penghindaran Pajak - Dinida Prilya; Fera Damayanti; Angga Permadi Karpriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to evaluate and analyze the impact of institutional ownership, proportion of independent commissioners and profitability (ROA &ROE) on tax avoidance. This research applies a quantitative approach with descriptive statistical methods. The population studied includes companies in the food and beverage sector listed on the Indonesia Stock Exchange from 2019 to 2023. Sample collection was carried out using purposive sampling technique, with a total sample of 60. The annual report of each company and data in the form of information from the IDX for data collection needs become secondary data. Multiple linear regression testing was carried out using SPSS version 26 software as a data processing tool. The findings of this study indicate that institutional ownership and return on equity (ROE) have a negative, but insignificant, impact on tax avoidance. Meanwhile, the proportion of independent commissioners has a positive and significant impact on tax avoidance and return on assets (ROA) has a positive but insignificant impact on tax avoidance.